Modeling long-term health outcomes of patients with cystic fibrosis homozygous for F508del-CFTR treated with lumacaftor/ivacaftor. (February 2019) - Rubin, Jaime L.; O'Callaghan, Lasair; Pelligra, Christopher; Konstan, Michael W.; Ward, Alexandra; Ishak, Jack K.; Chandler, Conor; Liou, Theodore G.
Background: Lumacaftor/ivacaftor combination therapy is efficacious and generally safe for patients with cystic fibrosis (CF) homozygous for the F508del-CF transmembrane conductance regulator (CFTR) mutation. However, long-term survival benefits of lumacaftor/ivacaftor (LUM/IVA) cannot yet be quantified. Simulation models can provide predictions about long-term health outcomes. In this study, we aimed to project long-term health outcomes of LUM/IVA plus standard care (SC) in patients with CF homozygous for F508del-CFTR . Methods: This modeling study was an individual patient simulation in US patients aged ⩾6 years with CF, homozygous for F508del-CFTR . The primary outcome was projected survival among (a) a cohort of patients who ever initiated LUM/IVA, accounting for treatment discontinuations, and (b) a cohort of patients who remain on continuous LUM/IVA. Patient characteristics and model parameters were derived from clinical trials: VX14-809-109, VX13-809-011B, TRAFFIC/TRANSPORT, and PROGRESS; published literature; and the US CF Foundation Patient Registry. Results: Lumacaftor/ivacaftor + SC is expected to increase median survival by 6.1 years versus SC alone, accounting for treatment discontinuations. The incremental median predicted survival versus SC assuming initiation of LUM/IVA at ages 6, 12, 18, and 25 years was 17.7, 12.6, 8.0, and 3.8 years, respectively. Assuming lifetime treatment with LUM/IVA, incremental median survival was predicted to be 7.8 years longer in the LUM/IVA + SC cohort. Initiating LUM/IVA at ages 6, 12, 18, and 25 years and assuming lifetime treatment resulted in incremental median predicted survival of 23.4, 18.2, 11.0, and 4.8 years, respectively. Conclusions: Lumacaftor/ivacaftor is projected to increase survival for patients with CF. Initiation at an early age and treatment persistence result in further increments in projected survival.